Comparative Study : Effect of Giving Fe Tablets and Moringa Leaves on Hb Levels in Pregnant Women - Sumarni Sumarni; Wijayanti, Eka Wahyu (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Overview: Normal Hemoglobin levels during pregnancy are very important in preventing anemia and complications that can occur during pregnancy. Moringa capsules contain iron, vitamin C, and antioxidants that can support the absorption of iron in the body, Fe tablets that support oxygen transport and the formation of red blood cells. Objective: Analyzing the effect of giving moringa leaf capsules and iron tablets on hemoglobin levels in pregnant women. Research Method: This study used a Quasi-experimental design method. This study was conducted in the Ambal II Kebumen Health Center Working Area with a sample of 30 respondents. In this study, 2 groups were used, namely those who received intervention (moringa leaf capsules and Fe tablets) and the control group (Fe only). Data analysis using the Wilcoxon test. Research Results: Showed that there was a difference in Hemoglobin levels in the Moringa leaf and Fe groups with a p value = 0.008 and as many as 14 pregnant women experienced an increase in Hb. While in the control group the analysis results showed a difference with a p value = 0.007. However, as many as 13 mothers experienced a decrease in Hb levels. Conclusion: giving moringa capsules and Fe tablets has better effectiveness in increasing Hb levels compared to just Fe tablets alone.